Policy Alignment to Sustainable Development Goals in Nepal - Adhikari, Sushma (Campion Journal of Multidisciplinary Research and Explorer, 2025)
These studies suggest that Nepal has made progress in aligning national and local policies with the Sustainable Development Goals, particularly in areas like poverty reduction, gender equality, and community forestry, but faces challenges such as limited resources, institutional capacity, policy coherence, and implementation gaps that hinder full and effective SDG integration. This research attempts to summarize the achievements and difficulties related to sustainable development by undertaking an extensive literature review on perspectives on sustainable development. Based on arguments and discussions of academics, researchers. The study employs a review-based technique. Sustainable development requires striking a balance between the three main pillars of social, economic, and environmental development in order to promote development narratives. The body of research concludes that Nepal must continue to align the prompt implementation of the SDGs even though it is making progress. Resource mobilization, strengthening international alliances, encouraging good governance and institutionalization, guaranteeing environmental resilience, and improving an integrated approach and equity are important initiatives that must be tackled up to Agenda 2030 of the Sustainable Development Goals.